Jesu Christi Zweifel(n) an Gott - Schelhas, Johannes 1961- (2017)
Dogmatics does not talk about the doubts of Jesus, even though it thinks about it. Jesus' prayer in Gethsemane probably implies his doubts. The result of this prayer to go forward strengthened flows from Jesus' doubt about the Father and his mission. Vaticanum I and its teaching about human cognition of God imply the impossibility of Jesus' doubts. But more recent studies of Jesus' self-awareness and sense of mission make it possible to reflect the doubts of Jesus as human person.
Keywords: Canavesio, Giovanni; Gethsemane-Erzählung; Leben-Jesu-Forschung; Glaube; Christologie